2006
DOI: 10.1111/j.0021-9029.2006.00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Directionality of the Association Between Social Support and Posttraumatic Stress Disorder: A Longitudinal Investigation1

Abstract: Healthcare SystemThis study examined the nature of the association between social support and posttraumatic stress disorder (PTSD) symptomatology among 2,249 male veterans of the 1990-1991 Gulf War. Using structural equation modeling, a cross-lagged panel analysis indicated a strong negative relationship between PTSD at Time 1 and social support at Time 2, while social support at Time 1 did not predict PTSD at Time 2. Findings suggest that, over time, interpersonal problems associated with PTSD may have a detr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
205
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(230 citation statements)
references
References 50 publications
14
205
1
Order By: Relevance
“…In line with the buffering model [11], the presence and utilization of positive social support resources has shown to promote natural recovery, thereby reducing negative outcomes for those who have experienced trauma [12]. Alternatively, the erosion model proposes that PTSD symptoms of social withdrawal and avoidance, numbing and detachment, and anger negatively affect the quality and quantity of received support by pushing away potential resources [13][14]. In support of this latter model, military veterans with PTSD have been shown to have intimacy and sociability difficulties, marital distress and relationship abuse, and parenting difficulties [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In line with the buffering model [11], the presence and utilization of positive social support resources has shown to promote natural recovery, thereby reducing negative outcomes for those who have experienced trauma [12]. Alternatively, the erosion model proposes that PTSD symptoms of social withdrawal and avoidance, numbing and detachment, and anger negatively affect the quality and quantity of received support by pushing away potential resources [13][14]. In support of this latter model, military veterans with PTSD have been shown to have intimacy and sociability difficulties, marital distress and relationship abuse, and parenting difficulties [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous quantitative studies have demonstrated that PTSD effects not only the veteran who has received the diagnosis, but several domains of family functioning i ncl udi ng fami ly cohesion, parenting satisfaction, relationship with spouse, self-identity of spouse, functioning and emotional security of children (Gavlovski and Lyons, 2004;King et al, 2006). Poor functioning in these domains has been correlated to higher rates of divorce and higher occurrences of clinically significant levels of relationship distress in the families of veterans with PTSD than in the families of veterans without PTSD or in the general population (Gavlovski and Lyons, 2004;King et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Poor functioning in these domains has been correlated to higher rates of divorce and higher occurrences of clinically significant levels of relationship distress in the families of veterans with PTSD than in the families of veterans without PTSD or in the general population (Gavlovski and Lyons, 2004;King et al, 2006). Veterans with PTSD are more likely than members of the general population to have clinically significant levels of depression, anxiety, anger, and violence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deleterious effects of PTSD on social support have been shown in longitudinal studies. Recent models suggest that PTSD symptoms contribute to the erosion of social support over time (King, Taft, King, Hammond, & Stone, 2006), which could indicate an opposite causal relationship between social support and PTSD symptoms. Indeed, changes in both social support and quality of life could be a consequence of changes in PTSD symptoms.…”
Section: Ptsd Social Support and Coping Strategies As Predictors Ofmentioning
confidence: 99%